Identifying the Efficacy of Extracellular Vesicles in Osteogenic Differentiation: An EV-Lution in Regenerative Medicine - Brown, Sarah V.; Dewitt, Sharon; Clayton, Aled; Waddington, Rachel J. (Frontiers in Dental Medicine, 2022)
Mesenchymal stromal cells (MSCs) have long been the focus for regenerative medicine and the restoration of damaged or aging cells throughout the body. However, the efficacy of MSCs in cell-based therapy still remains unpredictable and carries with it enumerable risks. It is estimated that only 3-10% of MSCs survive transplantation, and there remains undefined and highly variable heterogeneous biological potency within these administered cell populations. The mode of action points to secreted factors produced by MSCs rather than the reliance on engraftment. Hence harnessing such secreted elements as a replacement for live-cell therapies is attractive. Extracellular vesicles (EVs) are heterogenous lipid bounded structures, secreted by cells. They comprise a complex repertoire of molecules including RNA, proteins and other factors that facilitate cell-to-cell communication. Described as protected signaling centers, EVs can modify the cellular activity of recipient cells and are emerging as a credible alternative to cell-based therapies. EV therapeutics demonstrate beneficial roles for wound healing by preventing apoptosis, moderating immune responses, and stimulating angiogenesis, in addition to promoting cell proliferation and differentiation required for tissue matrix synthesis. Significantly, EVs maintain their signaling function following transplantation, circumventing the issues related to cell-based therapies. However, EV research is still in its infancy in terms of their utility as medicinal agents, with many questions still surrounding mechanistic understanding, optimal sourcing, and isolation of EVs for regenerative medicine. This review will consider the efficacy of using cell-derived EVs compared to traditional cell-based therapies for bone repair and regeneration. We discuss the factors to consider in developing productive lines of inquiry and establishment of standardized protocols so that EVs can be harnessed from optimal secretome production, to deliver reproducible and effective therapies.